Pre-service Biology Teachers’ Digital Competences Profile - Aidil Adhani; Nursia Nursia (Jurnal Pendidikan Indonesia Gemilang, 2024)
Education in the digital era increasingly demands teachers to have the ability to utilize technology as a tool in the learning process. Pre-service biology teachers need to understand and master various technologies related to the biology field, such as educational software, online learning platforms, and other digital media. This study aimed to objectively and comprehensively describe the profile of digital competence among biology pre-service teachers. This study utilizes a quantitative descriptive research design. The data collection uses a specially designed questionnaire to measure the digital competence of biology pre-service teachers. The research findings found that the average score of the average level of digital competency among pre-service biology teachers is 3.13, indicating a moderate level. The findings can be the basis for developing training programs and enhancing digital competence for pre-service biology teachers.